Occupational exposure to chlorinated solvents and risks of glioma and meningioma in adults. Issue 11 (3rd August 2012) - Neta, Gila; Stewart, Patricia A; Rajaraman, Preetha; Hein, Misty J; Waters, Martha A; Purdue, Mark P; Samanic, Claudine; Coble, Joseph B; Linet, Martha S; Inskip, Peter D
Abstract : Objectives: Chlorinated solvents are classified as probable or possible carcinogens. It is unknown whether exposure to these agents increases the risk of malignant or benign brain tumours. Our objective was to evaluate associations of brain tumour risk with occupational exposure to six chlorinated solvents (ie, dichloromethane, chloroform, carbon tetrachloride, 1, 1, 1-trichloroethane, trichloroethylene and perchloroethylene). Methods: 489 glioma cases, 197 meningioma cases and 799 controls were enrolled in a hospital-based case-control study conducted at three USA hospitals in Arizona, Massachusetts and Pennsylvania. Information about occupational history was obtained through a detailed inperson interview that included job-specific modules of questions such that the interview was tailored to each individual's particular work history. An industrial hygienist assessed potential solvent exposure based on this information and an exhaustive review of the relevant industrial hygiene literature. Unconditional logistic regression models were used to calculate OR and 95% CI for each solvent for ever/never, duration, cumulative, average weekly and highest exposure. Results: Overall, we found no consistent evidence of an increased risk of glioma or meningioma related to occupational exposure to the six chlorinated solvents evaluated. There was some suggestion of an association between carbon tetrachloride and glioma in analyses restricted to exposed subjects, with average weekly exposure above the median associated with increased risk compared with below the median exposure (OR = 7.1, 95% CI 1.1 to 45.2). Conclusions: We found no consistent evidence for increased brain tumour risk related to chlorinated solvents.